Integrating Coding and Project-Based Learning to Foster Elementary Students’ Creativity - Leni Agustina Daulay; Rahmah Nurfitriani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Despite growing interest in coding education for fostering 21st-century skills, empirical evidence from resource-constrained, non-metropolitan settings remains limited, particularly when comparing digital and non-digital approaches. This study investigated the comparative effectiveness of plugged and unplugged coding instruction within a Project-Based Learning (PjBL) framework in enhancing creative thinking skills among fifth-grade students. Using a mixed-methods quasi-experimental design, 98 students from two Integrated Islamic Elementary Schools in Central Aceh were assigned to a plugged coding group (n = 50) using Scratch 3.0 or an unplugged coding group (n = 48) using cardboard-based physical media. Creative thinking was assessed using TTCT-inspired open-ended project design tasks aligned with four Guilford dimensions (fluency, flexibility, originality, elaboration), while student perceptions and qualitative learning experiences were examined through questionnaires and semi-structured interviews. Both groups demonstrated significant pre–post improvement; however, the plugged group achieved a higher N-Gain (0.489 vs. 0.419), both within the moderate category, with a statistically significant but practically moderate between-group difference (p = .001, Cohen's d = 0.65). Qualitative findings indicated that plugged coding supports iterative refinement and multimedia expression, whereas unplugged coding promoted collaboration and flexible thinking through physical co-construction. Perception data showed positive learning experiences in both groups, with perceived creativity support moderately correlated with N-Gain scores in both conditions. These findings suggest that both approaches effectively support creative thinking through distinct pedagogical mechanisms and provide practical guidance for designing inclusive and context-sensitive coding instruction in resource-constrained elementary settings. This study compared the two approaches as separate conditions; hybrid integration was not examined.